2003
DOI: 10.1016/s0006-3495(03)74791-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Dynamics and Domain Formation in Model Membranes Composed of Ternary Mixtures of Unsaturated and Saturated Phosphatidylcholines and Cholesterol

Abstract: In recent years, the implication of sphingomyelin in lipid raft formation has intensified the long sustained interest in this membrane lipid. Accumulating evidences show that cholesterol preferentially interacts with sphingomyelin, conferring specific physicochemical properties to the bilayer membrane. The molecular packing created by cholesterol and sphingomyelin, which presumably is one of the driving forces for lipid raft formation, is known in general to differ from that of cholesterol and phosphatidylchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
196
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 218 publications
(222 citation statements)
references
References 55 publications
(62 reference statements)
24
196
1
1
Order By: Relevance
“…When cooling the GUVs from the miscibility temperature, the stripe domains appeared below the pretransition temperature of DPPC and became wider and more interconnected with further temperature decrease ( Figure 6). Independent FCS studies by Scherfeld et al (12) and Korlach et al (7) have showed that stripe domains in DOPC/DPPC and DLPC/DPPC GUVs have a diffusion rate close to pure DPPC below the transition temperature (35). Based on these previous studies and our observations, we propose that the stripe domains are in the gel phase.…”
Section: Discussionsupporting
confidence: 85%
“…When cooling the GUVs from the miscibility temperature, the stripe domains appeared below the pretransition temperature of DPPC and became wider and more interconnected with further temperature decrease ( Figure 6). Independent FCS studies by Scherfeld et al (12) and Korlach et al (7) have showed that stripe domains in DOPC/DPPC and DLPC/DPPC GUVs have a diffusion rate close to pure DPPC below the transition temperature (35). Based on these previous studies and our observations, we propose that the stripe domains are in the gel phase.…”
Section: Discussionsupporting
confidence: 85%
“…5B) and Bdp-cholesterol (Fig. 5C), classical markers of the L d (11) and sterol-enriched phases (82). Both fluorophores exhibited a spatial segregation in distinct domains (Fig.…”
Section: Di-4-aneppdhq Imaging Reveals Partitioning Of L O and L D Domentioning
confidence: 89%
“…5D). To discriminate between L o and L d phase, we considered a threshold limit of 1.2 for RGP because pure DOPC GUVs exist in a unique L d phase at room temperature (11,81) and consistently exhibit more than 95% of their RGP values greater than 1.2. In these conditions, the pattern obtained with di-4-ANEPPDHQ (Fig.…”
Section: Di-4-aneppdhq Imaging Reveals Partitioning Of L O and L D Domentioning
confidence: 99%
See 1 more Smart Citation
“…Single-molecule microscopy and single-molecule tracking has revealed detailed motions of membrane proteins such as micro-scale diffusion on cell surfaces revealing inhomogeneities of lipid rafts (Dietrich et al, 2002;Scherfeld et al, 2003;Schutz et al, 2000;Simons and Ikonen, 1997;Simons and Tommre, 2000) and cytoskeletal corrals (Kusumi and Sako, 1996) or the entry and intracellular fate of single viruses in living cells (Lakadamyali et al, 2003;Seisenberger et al, 2001). The tracking and observation of colocalization of individual proteins on cell surfaces is not only important in revealing microdiffusion but represents a physiological strategy to complement protein overexpression models and avoid nonphysiological cross talk of multiple signals generated from a single receptor or ion channel (Sako and Yanagida, 2003;Sako et al, 2000;Yoshiharu and Yanagida, 2002).…”
Section: Introductionmentioning
confidence: 99%